Kepentingan Rusia Melanjutkan Pembangunan Pipa Gas Turkstream Dengan Turki Tahun 2016 (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This research aims to describe the interests of Russia in continuing the construction of TurkStream gas pipeline with Turkey by using qualitative research methods. The TurkStream gas pipeline is one of the construction that Russia and Turkey needed, but the construction was delayed due to the shooting of Turkish military forces against the Russian military aircraft SU-24 on the Syrian border. The Researcher uses complex interdependence and national interests to analyze the pattern of relations between Russia and Turkey. This research perceives that Russia accepted an apology from Turkey and lifted economic sanctions against Turkey is willing to continue the construction of the TurkStream gas pipeline. This is based on Russia’s national interests and complex interdependence between Russia and Turkey especially in the defence interests, economic interests, and world order interests. Keywords: Russia-Turkey, T